A Comprehensive Analysis of Lymphoscintigraphy Results for Lower Limb Edema in Pediatric Group of Patients at NINMAS (Bangladesh Journal of Nuclear Medicine, 2024)
Background: The diagnosis and treatment of pediatric lymphedema provide particular challenges. The defining feature of lymphedema is aberrant interstitial fluid collection, which can be caused by a variety of factors, including acquired illnesses and congenital defects. This study used lymphoscintigraphy to determine the source of lymphedema in children of various ages. Patients and Methods: In this retrospective analysis, 53 children were included, who were referred to National Institute of Nuclear Medicine and Allied Sciences (NINMAS) for lower limb lymphoscintigraphy in the years 2022.2023. All pertinent facts and data were taken from the medical records. An average dosage of 1+1 mCi of 99m Technetium- (99m Tc) labeled nanocolloid was injected into the web spaces of the first and second toes of each foot. Spot views and delayed whole-body sweep images were acquired on time. Dual head gamma camera images were collected anterior and posteriorly. The assessment of the injection site, primary lymphatic channels, collateral vessels, dermal backflow, and quantity and strength of radiotracer absorption of the lymph nodes were all included in the qualitative image interpretation process. Result: The mean age was 10.14 years ± 5.37 with age ranging from 0-17 years. In 48/53 cases (90.6%) of clinically positive leg swelling were found to be positive for lymphedema on lymphoscintigraphy, where 16 patients had unilateral and 33 patients had bilateral. Remaining 05/53 (9.4%) were scintigraphically normal. Among the positive patients, 48 cases (98%) were primary lymphedema and only one (2%) had secondary cause, who was a case of bilateral lymphedema, Grade-I in left lower limb (LLL) and Grade-III in right lower limb (RLL). Conclusion: Lymphoscintigraphy, a non-invasive, straightforward imaging modality, is very helpful in precisely documenting and grading lymphedema for finding the etiology and subsequent treatment plans in patients with leg swelling. It also serves as a means of functional evaluation of lymphatic channels. Additionally, it can be crucial for individuals undergoing surgical procedures to relieve clinical symptoms early on in their recovery.Bangladesh J. Nuclear Med. 27(1): 75-80, 2024